Influences of different oxidants on the characteristics of HfAlO_x films deposited by atomic layer deposition - 樊继斌 刘红侠 马飞 卓青青 郝跃 (Chinese physics B, 2013)
A comparative study of two kinds of oxidants（H2O and O3） with the combinations of two metal precursors [trimethylaluminum（TMA） and tetrakis（ethylmethylamino） hafnium（TEMAH）] for atomic layer deposition（ALD） hafnium aluminum oxide（HfAlOx） films is carried out.The effects of different oxidants on the physical properties and electrical characteristics of HfAlOx films are studied.The preliminary testing results indicate that the impurity level of HfAlOx films grown with both H2O and O3 used as oxidants can be well controlled,which has significant effects on the dielectric constant,valence band,electrical properties,and stability of HfAlOx film.Additional thermal annealing effects on the properties of HfAlOx films grown with different oxidants are also investigated.